Um estudo sobre o endividamento público no Brasil e implicaç\~oes - Mário Jorge Cardoso de Mendonça; Tito Belchior Silva Moreira; Luis Alberto Toscano Medrano; George Henrique Cunha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This study aims to revisit the issue of the sustainability of public indebtedness in Brazil, investigating the evolution of gross debt of public sector, the relationship between its liabilities and assets of the public sector, the future implications of gross debt to net debt and to make forecast of the gross debt of the general government for the next two years. We show that the examination of the concept of net debt (gross debt less public sector assets) can cover up important questions about the public indebtedness.We ask if one can have some idea about the future behavior of net debt based on the present performance of gross debt. In this context, we conducted a Granger causality test between the net (DLGG) and gross debt (DBGG) of the general government. Empirical results show that DBGG Granger cause DLGG.We apply the Dynamic Factorial Model (MFD) to make forecast on the gross debt of public sector and its major components. The results display a strong rise in foreign debt and repurchase agreements. In August 2016 they reach, respectively, 10% and 17% of GDP. The results also show the forecast of the net debt (DLSP). It is shown that DLSP reaches 44% of GDP in August 2016. The GDP also shows sharp drop in economic activity. From September 2015 to August 2016 this variable decreases around 3.5%. Finally, we check the effect the indebtedness on economic growth. The empirical results show that the rise of both the gross and the net debt as a proportion of GDP has a negative effect on the growth rate of the GDP.
Keywords: H24; N46; E62; 330; gross and net indebtedness; economic grow; Granger causality test; dynamic factorial model